1995
DOI: 10.1021/j100018a043
|View full text |Cite
|
Sign up to set email alerts
|

An Orientational Study of Small Solutes in Zero Electric Field Gradient Nematic Liquid-Crystal Mixtures

Abstract: The solutes m-dichlorobenzene, o-dichlorobenzene, p-dichlorobenzene, o-dicyanobenzene, furan, tetrathiofulvalene, and fluorobenzene are studied in the zero electric field gradient mixtures 56.5 wt % 1132BBBA and 70 wt % 5CBBBBA using proton NMR. The two second-rank-order parameters obtained for each solute from analysis of the NMR spectra indicate that the solutes experience a similar anisotropic potential in both mixtures. The results are interpreted in tenns of two models for the short-range anisotropic pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…However, as we shall show below, a large body of data on solutes of varying sizes and shapes in mixtures where the electric field gradient experienced by molecular hydrogen is removed (zero efg mixtures) can be understood in terms of a single orientation mechanism. [43][44][45][46] The most likely candidate for such a mechanism is a short-range repulsive potential; this approach is consistent with the notion of the zero efg experienced by molecular hydrogen. The use of zero efg mixtures is quite general and not restricted to certain classes of solutes.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, as we shall show below, a large body of data on solutes of varying sizes and shapes in mixtures where the electric field gradient experienced by molecular hydrogen is removed (zero efg mixtures) can be understood in terms of a single orientation mechanism. [43][44][45][46] The most likely candidate for such a mechanism is a short-range repulsive potential; this approach is consistent with the notion of the zero efg experienced by molecular hydrogen. The use of zero efg mixtures is quite general and not restricted to certain classes of solutes.…”
Section: Introductionsupporting
confidence: 77%
“…The initial work on zero electric field gradient nematic liquid crystals utilized the mixture 55 wt % 1132 and 45 wt % EBBA at 301.4 K. Studies were carried out on a collection of solutes of varying sizes, shapes, and symmetries, including solutes that exist in more than a single conforma- tion. 29,31,34,36,39,[43][44][45][46]55,58,60,62,67,70,76,79,87,92,[99][100][101][102][103][104][105][106][107][108][109][110][111] It was found that phenomenological models for the anisotropic short-range interactions provided the best rationalization of the experimental results, which will be summarized in section VIII.…”
Section: Orientational Order In Zero Electric Field Gradient Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the x   values in [35]were found to be 12´2 6 2´0 and 19´7 6 3´6 for 70 wt% 5CB± EBBA and 56´5 wt% 1132± EBBA respectively. It should be noted that the parameters x   and k s are somewhat correlated, and the x   values obtained depend on the set of molecules chosen for the ® t [35].…”
Section: Downloaded By [Mcmaster University] At 04:12 27 December 2014mentioning
confidence: 90%
“…There are two points in ® gure 5, taken from [24,35] (`star' symbols), which correspond to the solutes ODCB and MDCB in another`zero efg mixture', 56´5 wt% 1132± EBBA. The reason for including the`star' symbols is to examine the e ect of temperature oǹ zero efg mixtures' .…”
Section: Biaxial Order Parametermentioning
confidence: 99%